2018
DOI: 10.1155/2018/4549154
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Low-Temperature Chemical Bath Deposition of CdS Thin Films without Thickness Limitation: Structural and Optical Properties

Abstract: In this work, thin CdS films have been deposited using the chemical bath deposition technique (CBD). Different synthesis parameters, such as number of runs, deposition time, and postannealing temperature, are studied and optimized in order to avoid the supersaturation phenomenon and to achieve a low-temperature growth. CdS thin films, of cubic structure, oriented along the (111) direction with homogenous and smooth surface, have been deposited by using the CBD growth process without any annealing treatment. Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…Together, these results indicate the n-type conductivity of the CdS-f layer with a donor concentration of N D = 4.2 × 10 17 cm –3 . These results, along with the XPS measurements shown in Figure b, suggest that the CdS-f films used in the conversion process, which transformed the CdS-f layer into a PtSM layer, exhibited similar properties to the CdS-f films previously demonstrated by M. Ouafi and co-workers in ref .…”
Section: Resultssupporting
confidence: 84%
“…Together, these results indicate the n-type conductivity of the CdS-f layer with a donor concentration of N D = 4.2 × 10 17 cm –3 . These results, along with the XPS measurements shown in Figure b, suggest that the CdS-f films used in the conversion process, which transformed the CdS-f layer into a PtSM layer, exhibited similar properties to the CdS-f films previously demonstrated by M. Ouafi and co-workers in ref .…”
Section: Resultssupporting
confidence: 84%
“…The electric field at the substrate–solution interface (Helmholtz layer) could be important in many cases during the nucleation process. It has been found that this field effect increases as the charge of the cation increases, so the adhesion of Cd + ions on the substrate surface may be more favored than that of Cd­(OH) + ions. , …”
Section: Methodsmentioning
confidence: 99%
“…This arrangement is capable of enhancing the crystallinity and the cubic phase. Moreover, it is responsible for the formation of the first layer on the substrate surface and controls the path of the reaction [65][66][67]. After specific time, the CdS molecules and [Cd(NH 3 ) 4 ] 2+ intermediate complexes began to collide with each other and molecule-by-molecule mechanism was started at this point to form cluster nuclei.…”
Section: Mechanismmentioning
confidence: 99%